The Influence Of Inquiry Learning On Students' Statistical Reasoning Abilities - Verra Yuniard; Suhar; Fahinu (FKIP Universitas Halu Oleo, 2024)
Education for Class VIII Students at SMP Negeri 2 Parigi is currently the main focus of scientific research. This research focuses on students' statistical reasoning in applying the Inquiry Model in class VIII. In addition, this research aims to evaluate the extent to which the Inquiry Model is applied in learning to improve the statistical reasoning abilities of class VIII students. This research method uses quasi-experimental research. Two classes were chosen as samples, namely the experimental class (class VIII 3) and the control class (class VIII 1). From the research results, several significant conclusions can be drawn. First, the statistical reasoning ability of class VIII students at SMP Negeri 2 Parigi who received learning using the Inquiry Model showed an average score of 70.0, median 71.85, and mode 81.2. On the other hand, students who received learning using the Direct Learning Model had an average of 63.64, a median of 53, and a mode of 50. Second, the implementation of learning using the Inquiry Model at SMP Negeri 2 Parigi from the level of teacher and student activity during four consecutive meetings reached a percentage 75%, 75%, 90%, and 90% for teachers, and 68.05%, 75%, 90.27%, and 91.66% for students. Therefore, the experimental class that applies the Inquiry Model is considered to meet the success criteria. Third, the results of statistical analysis show that the calculated t value is 1,766, exceeding the t table value of 1,671, with a significance level of 0.05